Letter - Winstanley, E.
030-0019-001 Telegraphic Address, Inland - "Wholesale, Manchester." Foreign - "Copexport, Manchester." Telephone: Blackfriars 1212. Extension No. 87 Please address your reply: CO-OPERATIVE WHOLESALE SOCIETY LIMITED, EXPORTERS, BUYING AND SHIPPING AGENTS, 1, BALLOON STREET, MANCHESTER, 4. Cable codes: A.B.C. 6th and 7th editions; Western Union 8 Letter; Bentley Complete Phrase; Bentley Second Phrase; A.I. Marconi, and private. OUR REFERENCE EXPORT 1733 ST/HP. YOUR REFERENCE 20th October, 1938. The Trades Union Congress, Transport House, Smith Square, LONDON. S.W.1. Cancel order for s.m. needles HVT Dear Sirs, We beg to make further reference to your order of the 15th instant, reference HVT/EAB, which included 800 Sewing Machine Needles. Unfortunately, our supplying Department have no knowledge of Werthein Machines, and they assume this to be a German model which they have never stocked, and for which they are unable to secure supplies of Needles. We regret, therefore, being compelled to exclude this line from your order. Difficulties have also arisen respecting the Singer and Jones Needles which you require. Our Department inform us that the style of Needle varies considerably according to the model for which it is intended, and although we can, of course, supply round and flat base Needles, medium and course, it is imperative that we know the model for which they are required, and we shall be glad if you will let us have this information if possible, when the order will receive our immediate attention. Yours faithfully, E. Winstanley Export Department. 292/946/30/19